2021
DOI: 10.1016/j.jss.2020.08.072
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19 Pandemic on Medical School Admissions: Challenges and Solutions

Abstract: Background The coronavirus disease 2019 (COVID-19) pandemic has brought hardship. With the pandemic, there is a need for more health care professionals; yet, premedical students face additional hurdles in applying to medical school. The process of applying to US medical schools before the COVID-19 pandemic was competitive, with an average acceptance rate of 6.7% in 2019. 1 Now with many unforeseen challenges, premedical students applying during 2020, 2021, and subsequent application cycles should be prepared f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…This curriculum may have particular value for premedical students during the COVID-19 pandemic, as students face even more limited opportunities to gain exposure to the realities of clinical practice[ 35 ]. Due to social distancing requirements, premedical students have been largely excluded from in-person experiences, and the American Medical Association has stated that they are unaware of how long these limitations will last[ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…This curriculum may have particular value for premedical students during the COVID-19 pandemic, as students face even more limited opportunities to gain exposure to the realities of clinical practice[ 35 ]. Due to social distancing requirements, premedical students have been largely excluded from in-person experiences, and the American Medical Association has stated that they are unaware of how long these limitations will last[ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…While many colleges and universities have found ways to transition these classes to virtual formats, these moves may jeopardize students that are struggling academically or require special attention. 1 Sani and associates promote the importance of finding creative ways for students to interact with one another commenting that a paucity of regular interactions amongst students can lead to high rates of burnout-an issue already plaguing prospective medical students and current trainees. 2 It has been demonstrated that interpersonal interactions with peers deepens the strength of learning new material for students.…”
mentioning
confidence: 99%
“…2 The authors also address changes brought about to the MCAT, namely the format of the examination and the scheduling issues with test site closures. 1 Another essential consideration is the effect that virtual coursework and unique stressors of the COVID-19 pandemic may have on student preparedness for the MCAT exam. The authors describe that virtual coursework has many negative consequences that may hinder the educational experience of the pre-medical student causing the student to be less prepared for the MCAT from their college coursework alone.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We would like to thank Gambril et al [1] for their interest and thoughtful comments on our paper analyzing the medical school admissions process in light of the COVID-19 pandemic. [2] Grambil et al show concern for students that are struggling academically or need special attention. We agree that there is need for an evaluation of the effect of virtual classes on academic performance, burnout rates, social challenges, and strength of learning.…”
mentioning
confidence: 99%